(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The supply chain is a network system composed of interconnected members such as suppliers, manufacturers, wholesalers, retailers and end customers. Inventory plays a major role in supply chain management and directly affects the cost and service quality of the entire supply chain system. Inventory control in the supply chain environment is not only closely related to a single enterprise itself, but also closely related to all enterprises in the supply chain. It is necessary to coordinate management with a holistic concept to achieve the overall optimal goal of the system. Aiming at the problems of low standardization in the field of power material management, material procurement plans and material demand plans are out of touch, and material inventory is too high, this article analyzes the problems of power material inventory management, researches and applies inventory control strategies, and combines its own corporate characteristics , Based on historical consumption data, extract and analyze the demand characteristics of electric power materials, and based on this to classify them scientifically and comprehensively, design the overall inventory control strategy of electric power materials, and build its dynamic inventory control model for different types of power materials , Realize the optimization and adjustment of inventory management, which can effectively improve the efficiency of inventory management and reduce the logistics management cost of the enterprise.